The Impact of Soft Skills of Project Managers in Construction Project Performance as the Mediation Role of a Conceptual Project Risk Management - Abdul-Kahar Adam , Nasser Salim Al Saadi , Madya Dr. Norhayati Binti Zakuan (International Journal of Advanced Science and Technology, 2020)
This paper is a conceptual data presentation and analysis on the impact of soft skills ofproject managers in the construction industry as the target survey has increased the demand forconstruction of infrastructure and facilities around the globe which is vital for rapid economicdevelopment. The methodology used in this study is a conceptual approach based on qualitativeanalysis of theoretical research and empirical data. The review of literatures and discussionsfrom previous studies showed that project management soft skills can be correlated with projectrisk management and project performance. It recommended future research of this topicquantitatively.